Nuevas especies y cambios taxonómicos para la herpetofauna de México - Flores-Villela, Oscar; Canseco-Márquez, Luis (Instituto de Ecología, A.C., 2020)
A compilation of the taxonomic and nomenclatural changes that affect the taxonomy of the Mexican speciesof amphibian and reptiles is presented. In the same manner, a list of newly described species, as well as newspecies recorded for Mexico in the last eleven years is presented. These changes and additions are compiled toDecember 2003. With this information, the number of Mexican species of amphibians and reptiles is elevated from997 to 1165, since the publication of the last list of Mexican herpetofauna.